Development of Learning Media for Video Audio-Visual Stop Motion Based on Contextual Teaching and Learning in Science Learning Water Cycle Material - Mufidah, Ismah; Nulhakim, Lukman; Alamsyah, Trian Pamungkas (Universitas Pendidikan Ganesha, 2020)
Learning done conventionally often makes students bored and less motivated to learn. In this time of the pandemic, the use of technology-based media such as audio-visual learning videos can become one of the ways for teachers to create effective learning. Audio-visual learning media are developed to make it easier for teachers to deliver learning materials. By developing technology-based media, online learning can be accomplished. The purpose of this research is to know the development and feasibility of media learning audio-visual video stop motion based contextual teaching and learning. The study employs research design and development. The development of audio-visual media videos stops motion based contextual teaching and learning is expected to make online learning during the pandemic more effective, efficient, and useful in elementary school.